2018
DOI: 10.3174/ajnr.a5809
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Assessment of Multispectral Voxel-Based Morphometry in Previously MRI-Negative Focal Epilepsy

Abstract: BACKGROUND AND PURPOSE: Voxel-based morphometry is widely used for detecting gray matter abnormalities in epilepsy. However, its performance with changing parameters, smoothing and statistical threshold, is debatable. More important, the potential yield of combining multiple MR imaging contrasts (multispectral voxel-based morphometry) is still unclear. Our aim was to objectify smoothing and statistical cutoffs and systematically compare the performance of multispectral voxel-based morphometry with existing T1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 26 publications
3
20
0
3
Order By: Relevance
“…It has been previously shown that the selection of smoothing (12 mm with T1 as reference) as well as statistical threshold ( t ‐score = 3.7) affected the detection rates in MRI‐negative cohort (Kotikalapudi et al, ). In the current study, a smoothing of 14 mm at a liberal T‐threshold of 3.3, gave the optimal trade‐off between specificity and concordant rate for the MP2 contrast.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been previously shown that the selection of smoothing (12 mm with T1 as reference) as well as statistical threshold ( t ‐score = 3.7) affected the detection rates in MRI‐negative cohort (Kotikalapudi et al, ). In the current study, a smoothing of 14 mm at a liberal T‐threshold of 3.3, gave the optimal trade‐off between specificity and concordant rate for the MP2 contrast.…”
Section: Discussionmentioning
confidence: 99%
“…The method to estimate the diagnostically ideal smoothing and T‐threshold has already been explained in detail in our previous work (Kotikalapudi et al, ). In brief, a single‐channel VBM variant is considered as a reference, that is, MP2 in our case.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations